Studi Sistem-Sistem Kebudayaan Masyarakat Arab Pra Islam - Rahmadani, Rahmadani; Daulay, Haidar Putra; sumanti, solihah titin (Journal Of Human And Education (JAHE), 2024)
The study of the socio-cultural life of pre-Islamic Arab society is important for understanding the transformation that occurred after the arrival of Islam. In the social aspect, pre-Islamic Arab society was known for its strong social staffing, from nobles to slaves, which determined the role of individuals in society. This research aims to further explore the socio-cultural dynamics of pre-Islamic Arab society, including social systems, cultural values, gender relations, and their influence on the development of Islam in the future. This research uses a qualitative method with a descriptive historical approach. Data was collected through library studies from primary sources such as classical Arabic literature, including historical works such as Sirah Nabawiyah and Tarikh al-Umam wa al-Muluk by Al-Tabari, and relevant sources such as scientific journals, articles, documents official, and other library sources, as well as secondary sources in the form of relevant modern studies. The results of this research state that tribal solidarity in the life of Arab society before Islam was known to be very strong, so that individual disputes almost always gave rise to conflict between tribes. Individually, Arabs would rather leave their homeland than submit to orders. They will not obey any regulations in force or any institution in power. They only know personal freedom, family freedom, and complete tribal freedom. This is because a man's relationship with his brother, his brother's children and his relatives is very close. However, the tribe's fanaticism is so high that they are even willing to die because of this fanaticism, because the basis of their social rules is racial and clan fanaticism. In terms of relationships between men and women, there are striking differences between society with noble social strata and other strata. Women are one group in society that almost never enjoy freedom, because apart from having to submit to the structures above them, they also have to submit to men in the structure of society. Keyword: Social, Cultural, Pre-Islamic Arabia